PERSEPSI PETERNAK SAPI POTONG TERHADAP PEMANFAATAN TEKNOLOGI BIOGAS DI KECAMATAN PASER BELENGKONG KABUPATEN PASER - Muhammad Tohri; Julinda Romauli Manullang; Mursidah Mursidah (Universitas Mulawarman, 2019)
ABSTRACT Purpose of this research was to know the perception farmer in the utilization of the technology biogas and to know whether there was the relationship between the parception with the implementation of the technology biogas Selection of a group of cattle was done by means of purposive sampling and retrieval of the respondents with technique porportionate random sampling with the number of 27 people. The perception of the farmers was measured with einght indicators by using a likert scale. Testing to determine the level of adoption of farmers towards biogas technology was measured from the four indicators of the level of implementation of biogas technology. To determine the relationship between the perception of the breeders and the application of biogas technology used in the analysis the chi-squared (ᵪ 2). Results of the research suggests that the farmer’s perception to the technology biogas show perception positive and the value of the implementation of the positive, it can be seen from the value of ᵪ 2 count of 3,14 and the value was bigger than the vaule of ᵪ 2 2,920 tabel. Untilᵪ 2 calculated ≥ ᵪ 2 of the tabel (0,05), then Ha acceptance H0 push. Perception farmer against the technology biogas positive, the implementation of the technology biogas by the farmer positive, and there was a relationship perception farmer with the implementation of the technology biogas.